Acute exposure to evening blue‐enriched light impacts on human sleep. (20th March 2013) - Chellappa, Sarah L.; Steiner, Roland; Oelhafen, Peter; Lang, Dieter; Götz, Thomas; Krebs, Julia; Cajochen, Christian
Summary Light in the short wavelength range (blue light: 446–483 nm) elicits direct effects on human melatonin secretion, alertness and cognitive performance via non‐image‐forming photoreceptors. However, the impact of blue‐enriched polychromatic light on human sleep architecture and sleep electroencephalographic activity remains fairly unknown. In this study we investigated sleep structure and sleep electroencephalographic characteristics of 30 healthy young participants (16 men, 14 women; age range 20–31 years) following 2 h of evening light exposure to polychromatic light at 6500 K, 2500 K and 3000 K. Sleep structure across the first three non‐rapid eye movement non‐rapid eye movement – rapid eye movement sleep cycles did not differ significantly with respect to the light conditions. All‐night non‐rapid eye movement sleep electroencephalographic power density indicated that exposure to light at 6500 K resulted in a tendency for less frontal non‐rapid eye movement electroencephalographic power density, compared to light at 2500 K and 3000 K. The dynamics of non‐rapid eye movement electroencephalographic slow wave activity (2.0–4.0 Hz), a functional index of homeostatic sleep pressure, were such that slow wave activity was reduced significantly during the first sleep cycle after light at 6500 K compared to light at 2500 K and 3000 K, particularly in the frontal derivation. Our data suggest that exposure to blue‐enriched polychromatic light at relatively low room light levels impacts upon homeostatic sleep regulation, as indexed by reduction in frontal slow wave activity during the first non‐rapid eye movement episode.